Potential bidirectional regulatory effects of botanical drug metabolites on tumors and cardiovascular diseases based on the PI3K/Akt/mTOR pathway - Ma, Su-ya; Liu, Yong-mei; Wang, Jie (Frontiers in Pharmacology, 2025)
Pharmacological interventions targeting the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway are predominantly employed as anticancer therapies, yet they are frequently associated with significant cardiac toxicity. Additionally, the PI3K/Akt/mTOR pathway plays a crucial role in the treatment of cardiovascular diseases, highlighting its dual significance in both oncology and cardiology. Therefore, the PI3K/Akt/mTOR pathway has become an ideal signaling pathway for studying cardioprotection, anticancer effects, and their associated cardiac toxicity. Botanical drugs have emerged as a significant source for developing therapeutic agents with anticancer and cardioprotective effects, often exhibiting bidirectional protective properties. Consequently, this study investigates the bidirectional regulatory influence of botanical drug metabolites in oncology and cardiology via the PI3K/Akt/mTOR pathway. The research indicated that the PI3K/Akt/mTOR signaling pathway plays a critical regulatory role in the pathogenesis of both tumors and cardiovascular diseases. The botanical drug metabolites Ruscogenin, Sulforaphane, Naringenin, Kaempferol, Poncirin, and Puerarin can improve cancer by inhibiting the phosphorylation levels within the PI3K/Akt/mTOR signaling cascade. Moreover, they also provide cardioprotective effects in cardiac injury conditions by activating the phosphorylation levels of the PI3K/Akt/mTOR pathway. Therefore, the phosphorylation dynamics of key components in the PI3K/Akt/mTOR pathway, particularly the phosphorylation of Akt, along with the functional implications of different phosphorylation sites, may offer new therapeutic strategies and insights for cancer treatment and the mitigation of cardiotoxicity associated with cancer therapies.